2016
DOI: 10.1038/aps.2016.102
|View full text |Cite
|
Sign up to set email alerts
|

Betulin from Hedyotis hedyotidea ameliorates concanavalin A-induced and T cell-mediated autoimmune hepatitis in mice

Abstract: Hedyotis hedyotidea has been used in traditional Chinese medicine for the treatment of autoimmune diseases. However, the mechanisms underlying for the effect remain unknown. We previously showed that, among 11 compounds extracted from H hedyotidea, betulin produced the strongest suppressive effect on T cell activation. Here, we examined the hepatoprotective effects of betulin against acute autoimmune hepatitis in mice and the mechanisms underlying the effects. Freshly isolated mouse splenocytes were stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Pharmacokinetic research in rats has showed that daily intraperitoneal administration of 60 mg/kg of betulin for 28 days does not result in toxicity [37]. Oral administration of 5 and 10 mg/kg betulin improved the scopolamine-induced amnesia in mouse models, and intraperitoneal administration of betulin (10 and 20 mg/kg) improved autoimmune hepatitis in mice [11,38]. Additionally, betulin administration (10 mg/kg) significantly decreased lung metastasis of CT26 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic research in rats has showed that daily intraperitoneal administration of 60 mg/kg of betulin for 28 days does not result in toxicity [37]. Oral administration of 5 and 10 mg/kg betulin improved the scopolamine-induced amnesia in mouse models, and intraperitoneal administration of betulin (10 and 20 mg/kg) improved autoimmune hepatitis in mice [11,38]. Additionally, betulin administration (10 mg/kg) significantly decreased lung metastasis of CT26 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, great attraction is paid to the use of natural products as new therapeutic and preventive drugs against immune-mediated hepatic injury due to their high efficiency, high safety, and low cost. Some compounds of natural products have been investigated to possess protective effects on immune hepatic injury [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that Con A can induce production of several proinflammatory factors, such as iNOS and a variety of proinflammatory cytokines including IL‐4, IL‐6, IL‐1β, IFN‐γ, and TNF‐α (Bai et al, , Liang et al, ). Since Con A challenge mimics the inflammation condition, Con A‐induced splenocytes proliferation model is commonly used to study immune‐mediated diseases (Demenesku et al, , Sharma & Tiku, , Zhou et al, ). GLG was found to concentration‐dependently inhibit Con A‐induced cell proliferation in isolated mice splenocytes, suggesting that GLG suppressed the activation of T‐lymphocytes under inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally known that LPS stimulates B‐lymphocyte proliferation response (Liu et al, ). However, inflammation involves both B‐lymphocyte and T‐lymphocyte proliferation (Xu et al, , Zhou et al, ). In order to investigate whether GLG's antiinflammatory and immunomodulatory effects involve T‐lymphocyte proliferation, the present study evaluated its effects on in vitro concanavalin A (Con A)‐induced proliferation/inflammation in BALB/c mice isolated splenocytes.…”
Section: Introductionmentioning
confidence: 99%